2007
DOI: 10.1016/j.cell.2007.04.039
|View full text |Cite
|
Sign up to set email alerts
|

SRC-3 Coactivator Functional Lifetime Is Regulated by a Phospho-Dependent Ubiquitin Time Clock

Abstract: SRC-3/AIB1 is an important growth coactivator whose activity should be tightly regulated since excess activation results in oncogenesis. Herein, we provide evidence that coordinated phosphorylation-dependent ubiquitination regulates SRC-3 coactivator activation and transcriptional specificity. We discovered a critical "actron/degron" element in SRC-3 that is required for this phosphorylation-dependent ubiquitination event and identified GSK3 and SCF(Fbw7alpha) as the respective responsible kinase and E3 ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
199
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 213 publications
(210 citation statements)
references
References 31 publications
10
199
0
1
Order By: Relevance
“…Results are consistent with numerous previous studies that demonstrate the phosphorylation of SRC-3 in response to estrogen, TNFa, epidermal growth factor, and RA (12,13,15,17,18,26,27). It has been shown that phosphorylation of SRC-3 affects the nuclear localization and interaction of the nuclear receptors with this coactivator as well as receptor-promoter interactions in response to various stimuli, thereby regulating cellular transcriptional activity (15,17,26). It has been proposed that phosphorylation of SRC-3 in response to RA initially promotes transcriptional activation with subsequent inhibition of RA-target genes as a result of SRC-3 degradation following prolonged RA exposure (13).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results are consistent with numerous previous studies that demonstrate the phosphorylation of SRC-3 in response to estrogen, TNFa, epidermal growth factor, and RA (12,13,15,17,18,26,27). It has been shown that phosphorylation of SRC-3 affects the nuclear localization and interaction of the nuclear receptors with this coactivator as well as receptor-promoter interactions in response to various stimuli, thereby regulating cellular transcriptional activity (15,17,26). It has been proposed that phosphorylation of SRC-3 in response to RA initially promotes transcriptional activation with subsequent inhibition of RA-target genes as a result of SRC-3 degradation following prolonged RA exposure (13).…”
Section: Discussionsupporting
confidence: 81%
“…Data indicate that the decrease of SRC-3 induced by ATRA in neurons is p38 MAPK but not ERK MAPK dependent. It has been shown that selective SRC-3 phosphorylation regulates the turnover of this coactivator by ubiquination and proteasomal degradation (13,17). The decrease of SRC-3 in the cultured neuron cells occurred several hours later than the phosphorylation of SRC-3 observed in the current study, and this decrease was prevented by MG132, a specific proteasome inhibitor.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Besides, the SRC family functions as coactivators not only for NR but also for multiple other transcriptional factors (TF), such as nuclear factor kappa B, E2F1 and IGF-1-dependent TFs (York et al, 2010;Ma et al, 2011;Walsh et al, 2012). By coactivating NR and these NFs, all members of the SRC family can modulate diverse genes expression programs and play important roles in growth, metabolism, reproduction and turmorigenesis (Wu et al, 2007;Coste et al, 2008;Yi et al, 2008;Cai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%